Diseases of Pomegranate (Punica granatum) in Florida - Katia Viana Xavier; Achala Nepal KC; Gary Edward Vallad (EDIS, 2019)
Pomegranate production is becoming increasingly popular in the Southeast. Florida’s humid subtropical to tropical climate is favorable for not only pomegranate tree establishment, but also several diseases. This new 5-page publication of the UF/IFAS Plant Pathology Department, written by Katia V. Xavier, Achala N. KC, and Gary E. Vallad, describes the various diseases affecting pomegranate in Florida and provides some management recommendations. https://edis.ifas.ufl.edu/pp349